Free Cash Flow, Shareholder Value, and the Undistributed Profits Tax of 1936 and 1937 - CHRISTIE, WILLIAM G.; NANDA, VIKRAM (Journal of Finance, 1994)
ABSTRACT In 1936, the Federal Government unexpectedly imposed a tax on undistributed corporate profits. Despite the direct costs of the tax, its announcement produced a positive revaluation of corporate equity, particularly among lower‐payout firms. We interpret this as evidence of a divergence between managerial and shareholder preferences regarding dividend payout policies, consistent with the presence of agency costs. We also find that despite the incentives created by the tax, the actual growth in dividends during 1936 was lower among firms judged more likely to be subject to higher agency costs after controlling for liquidity, debt, and the growth in earnings.